Ocean Current Energy Conversion System in Wallacea Region Using Variable Speed Control Approach - Aditya Sukma Nugraha; Estiko Rijanto (National Research and Innovation Agency, 2010)
Ocean Current Energy Conversion System (OCECS) is a promising green energy resource in this globe. The Thermohaline circulation data indicates that the Wallacea region has the potential of ocean current energy resources. This paper is aimed to propose research and development of OCECSs to be implemented in the Wallacea region. Firstly, four types of green energy conversion systems extracted from ocean are reviewed. Their advantages and disadvantages are discussed. Secondly, the potential of OCECS in the Wallacea region is described. Third, many types of turbines used for OCECS are reviewed and the turbine type for OCECS is selected to be implemented in the Wallacea region. Fourth, control strategy is proposed.From the work reported in this paper it is concluded that it is appropriate to implement OCECSs using axial flow water turbines in the Wallacea region, and that to maximize energy conversion variable speed control approach is selected together with control of mechanism to move the turbine vertically as well as to rotate the turbine in yaw direction.